A Model for Building AIS Capabilities in Co-operatives - Harun Rasit, Mohd Hadzrami; Ibrahim, Mohammad Azhar (Human Resource Management Academic Research Society, 2018)
Studies examining the link between information systems (IS) resources and organisation capabilities are extensive. However, limited studies were conducted to examined the influence of IS resources on AIS capabilities particularly in co-operatives. Based on a comprehensive review of accounting and IS literature, this paper propose a model to assessing the link between IS resources and accounting information systems (AIS) capabilities, and its potential impact on cooperatives performance.The model is based on the resource-based view (RBV) that is used to define various dimensions of IS resources. This paper proposes seven IS resources that include external relationships; IS infrastructure; IS technical skills; business knowledge; internal relationships; IS planning and change management; and last but not least IS development. Apart from establishing a model for AIS capabilities building, this paper contributes to the literature by providing a better understanding on the roles of IS resources in AIS capability-building. This paper further contributes in extending IS research by exploring the AIS implementation within cooperatives environment.